ADVANCED AMPLITUDE CENTERING AS AN INVIGORATING MANIPULATION FOR UNIFIED WAVELENGTH SPECTRAL RESOLUTION OF TERNARY MIXTURES - Lotfy, Hayam M.; Saleh, Sarah S. (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: This work presented the novel spectrophotometric approach namely, advanced amplitude centering (AAC). The method was applied for the resolution of ternary mixtures with partially or completely overlapped spectra. Methods: Advanced amplitude centering was based on the determination of ternary mixtures using single divisor where the concentrations of the components are determined through progressive manipulation performed on the same ratio spectrum. The centered amplitude at unified wavelength was resolved and applied for the determination of three components with partially and severely overlapped spectra. The work discussed the applications and advantages of the novel univariate advanced amplitude centering compared to the chemometric model, partial least square (PLS). Results: The specificity of the proposed methods was checked using laboratory-prepared mixtures of amlodipine (AML), valsartan (VAL) and hydrochlorothiazide (HCT) and was successfully applied for the analysis of two pharmaceutical formulations. The validity of results was assessed by applying the standard addition technique. Conclusion: The results obtained were found to agree statistically with those obtained by a reported method, showing no significant difference with respect to accuracy and precision.